The relationships between age and running biomechanics - DeVita, P.; Fellin, R. E.; Seay, J. F.; Ip, E.; Stavro, N.; Messier, S. P. (Medicine & Science in Sports & Exercise, 2016)
Running has high injury rates, especially among older runners. Most aging literature compares young with old runners without accounting for the progression of biomechanics throughout the lifespan. We used age as a continuous variable to investigate the continuum of age-related gait adaptations in running along with determining the chronology and rate of these adaptations.